INOVASI SEBAGAI MEDIATOR ANTARA KEPEMIMPINAN TRANSFORMASIONAL, SELF-EFFICACY, DAN KINERJA PEGAWAI - Juarini, Nisa; Indrawati, Mei (Program Studi Magister Manajemen, Direktorat Pascasarjana, Universitas Sangga Buana, 2024)
This study aims to describe the condition of performance, innovation, transformational leadership and work self-efficacy in the Bojonegoro Regency Transportation Agency. In addition, it is also to analyze the direct and indirect influence of leadership and work self-efficacy on performance through employee innovation. This study is classified as an Explanatory Research type with a quantitative approach. The population studied was all employees of the Bojonegoro Regency Transportation Agency, totaling 64 people. The research sample was determined as many as 64 people with the total sampling method. The data analysis technique used Path Analysis through the Partial Least Square (PLS) method. From the results of the analysis, it was concluded that transformational leadership, innovation and performance of employees of the Bojonegoro Regency Transportation Agency were in good condition, only employee self-efficacy was very good. Transformational leadership had a significant effect on employee innovation. Self-efficacy had a significant effect on employee innovation. Transformational leadership directly had a significant effect on employee performance. Self-efficacy did not have a significant effect on employee performance. Innovation had a significant effect on employee performance. Transformational leadership had a significant effect on performance through employee innovation. Self-efficacy had a significant effect on performance through employee innovation.